Designing devices to communicate effectively with intensive care nurses to prevent pressure injuries: A qualitative study. (August 2022) - Kovach, Jamison V.; Pollonini, Luca
Highlights: Incorporate users' needs into the design of devices to reduce pressure injuries. Communicate skin condition information in easy-to-understand summary displays. Provide reminders to take action when needed, without excessive interruptions. Use visual signals to indicate warnings/critical situations, not audible alarms. Capitalize on teamwork by providing a way to request help from others, as needed. Abstract: Objectives: The aim of this research was to identify "what" key design elements of a device for detecting hospital acquired pressure injuries should do and "how" these elements should function. The goal of the resulting design was to prompt intensive care unit nurses to intervene appropriately to reduce the incidence/severity of pressure injuries, while minimizing workflow disruptions. Methods: A mixed method study was performed in an intensive care unit, which included shadowing, interviewing, surveying and conducting focus groups with individuals knowledgeable about pressure injuries and related patient care. This study focused on identifying and prioritizing the needs/wants of nurses regarding devices aimed at detecting hospital acquired pressure injuries. These needs were then used as the foundation for designing key elements of such a device. Findings: Intensive care nurses indicated that a device for the early detection of pressure injuries should communicate information as real-time summaries about the severity of a skin issue in an easy-to-understand manner and provide reminders for them to take action when needed without unnecessarily interrupting their workflow. Conclusion: The findings regarding nurses' needs will be useful for the future development of technologies/devices that help reduce the incidence/severity of hospital acquired pressure injuries. In turn, nurses may be more likely to use such a device to enhance patient care.